MULTIPLE STREAMS FRAMEWORK DALAM PERWALI NOMOR 5 TAHUN 2023 TENTANG PUSAT INFORMASI SAHABAT ANAK SEBAGAI UPAYA PENGEMBANGAN KOTA LAYAK ANAK DI KOTA SURABAYA - Ria, Catur Ajeng Kartika; Hariyoko, Yusuf; Basyar, M. Roisul (Politeknik STIA LAN Makassar, 2024)
Surabaya is the second largest city in Indonesia, and it has a dynamic social fabric and faces various socio-cultural challenges. Despite these conditions, Surabaya has maintained its status as a primary child-friendly city for six consecutive years. The research aims to describe and analyze the agenda-setting process, consisting of three streams: the problem stream, the political stream, and the policy stream, in developing Surabaya as a child-friendly city. This study employs a qualitative approach, gathering primary data through interviews, observations, documentation, and secondary data collected from relevant documents. This research indicates that the policy stream predominantly influences the agenda-setting process in the development of Surabaya as a child-friendly city. The policy stream plays the most significant role, leading to the emergence of various alternative solutions in the development of Surabaya as a child-friendly city. Other factors influencing the development of Surabaya as a child-friendly city include the availability of facilities and innovative child rights fulfillment, government commitment, public awareness, and the involvement of Non-Governmental Organizations (NGOs).